Penerapan Theory Of Constraints (TOC) Untuk Optimalisasi Laba Pada PT. Perkebunan Nusantara VIII - Dinda Kirana Pelangi; Rahma Nazila Muhammad (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This research aims to provide an overview of the implementation of the Theory Of Constraints (TOC) on profit optimization by providing alternative solutions and calculating estimated profit in accounting at PT. Perkebunan Nusantara VIII. Data analysis uses the five-focusing steps developed by Goldratt. Before the implementation of the TOC, the cost of production was considered good, but sales needed to be increased to overcome losses, in March 2021 the loss for tea products was Rp. 20,159,000,000. After implementing the TOC with the first alternative, increasing sales in the Industri Hilir Teh through TikTok's contribution in supporting online marketing, the loss is estimated to be reduced by 0.5%. By implementing the second alternative, allocating banner expense for Facebook ads with local targets, the loss is reduced by 43% and for the overall sales target, it is estimated to reduce the loss by 53%.